Elements of integrated care approaches for older people: a review of reviews - Briggs, Andrew; Valentijn, P.; Thiyagarajan, J.; de Carvalho, I. (BM J Group, 2018)
Objective: The World Health Organization (WHO) recently proposed an Integrated Care for Older People approach to guide health systems and services in better supporting functional ability of older people. A knowledge gap remains in the key elements of integrated care approaches used in health and social care delivery systems for older populations. The objective of this review was to identify and describe the key elements of integrated care models for elderly people reported in the literature. Design: Review of reviews using a systematic search method. Methods: A systematic search was performed in MEDLINE and the Cochrane database in June 2017. Reviews of interventions aimed at care integration at the clinical (micro), organisational/service (meso) or health system (macro) levels for people aged =60 years were included. Non-Cochrane reviews published before 2015 were excluded. Reviews were assessed for quality using the Assessment of Multiple Systematic Reviews (AMSTAR) 1 tool. Results: Fifteen reviews (11 systematic reviews, of which six were Cochrane reviews) were included, representing 219 primary studies. Three reviews (20%) included only randomised controlled trials (RCT), while 10 reviews (65%) included both RCTs and non-RCTs. The region where the largest number of primary studies originated was North America (n=89, 47.6%), followed by Europe (n=60, 32.1%) and Oceania (n=31, 16.6%). Eleven (73%) reviews focused on clinical 'micro' and organisational 'meso' care integration strategies. The most commonly reported elements of integrated care models were multidisciplinary teams, comprehensive assessment and case management. Nurses, physiotherapists, general practitioners and social workers were the most commonly reported service providers. Methodological quality was variable (AMSTAR scores: 1-11). Seven (47%) reviews were scored as high quality (AMSTAR score =8). Conclusion: Evidence of elements of integrated care for older people focuses particularly on micro clinical care integration processes, while there is a relative lack of information regarding the meso organisational and macro system-level care integration strategies.